Synergistic effect of adding lignin and carbon black in poly(lactic acid) - Ferreira da Silva,Thaís (2020)
Abstract Antistatic packaging is a very important sector since the electrostatic discharge of electronic devices can damage and/or disable these products. In addition, it is essential to dispose of this packaging correctly. In this work, the synergistic effect of the addition of lignin and carbon black on the development of antistatic and biodegradable packaging was verified. In this study, PLA was mixed with lignin and carbon black and the composites were prepared using a high-speed thermokinetic homogenizer where the melting of the PLA and the blend with fillers occurred by friction. The composites were characterized by Izod impact tests, scanning electron microscopy, thermal properties, electrical characterization and biodegradation tests in garden soil. The results show that lignin is a great option to accelerate the biodegradation of PLA in the garden soil and the carbon black acts as an antistatic agent reducing the electrical resistivity of the composites.